Enabling anonymous crime reporting on mobile phones in the developing world - Burke, Mark John (Department of Computer Science, 2014)
Various campaigns indicate that a need exists for a convenient and anonymous crime reporting framework for the context of the developing world. In this thesis a contribution is made by means of a framework that facilitates reporting crime anonymously based on a secure platform. The framework comprises of two main components namely, a reporting module that is facilitated by unstructured supplementary service data (USSD) on a mobile phone and an anonymization module that is supported by a k-anonymity algorithm. The advantage of using USSD is that it is available to all mobile phones (including the more basic/nonsmart phones that are used by a large percentage of the poorer population in developing countries); and reports made via USSD cannot be traced to the participant. Anonymization has the advantage of guaranteeing user privacy in the management of the reported data. In order to decide on an appropriate anonymization technique for the crime reporting system, we implemented and compared existing popular k-anonymity based algorithms as well as suggesting a crime data anonyimzation algorithm tailored for specific sets of data. The proposed crimemod algorithm is found to provide satisfactory performance and security results. Our results indicate that anonymization algorithms that use hierarchy based generalization techniques, are the best suited to crime reporting scenarios.